Crop diversification level and its determinants in Ethiopia - Tamrat Gebiso; Mengistu Ketema; Arega Shumetie; Getachew Leggesse (Cogent Food & Agriculture, 2023)
AbstractCrop diversification is the cultivation of more than one variety of crops belonging to the same or different species in a given area to develop a resilient agricultural system. In Ethiopia, crop diversification is recognized as a strategy to improve nutrition and climate risk coping mechanisms. Despite the national aspiration to use crop diversification as a mechanism to ensure nutritional security and increase agricultural production, this effort has not been investigated in the central and southern Oroima where cereal production is dominating. The area is commonly known as the wheat belt of Ethiopia. Accordingly, this study was initiated to estimate the crop diversification level and identify the core drivers. The research was conducted in the central and northern Oromia region, Ethiopia. Four districts were selected from which a total of 390 household respondents were selected randomly. Simpson Diversification Index (SDI) was employed to estimate the crop diversification level, while ordered logit was employed to identify its determinants. Accordingly, about 25, 44, and 31% of the households were low, medium, and high diversifiers, respectively. Mitigating market and price risk (73%) and risk of crop failure (62%), food self-sufficiency (63%), and diversifying labor pressure during peak agricultural seasons (17%) were significant reasons for diversification. Family size, landholding, level of farm mechanization, land fragmentation, and spatial location strongly determine crop diversification levels. Improving access to farm mechanization, including irrigation technologies, and availing of alternative crop varieties by agricultural research institutes shall be given emphasis to improve crop diversification level.